Childhood, teenage and young adult cancer diagnosis during the first wave of the COVID-19 pandemic: a population-based observational cohort study in England. Issue 8 (22nd March 2022) - Saatci, Defne; Oke, Jason; Harnden, Anthony; Hippisley-Cox, Julia
Abstract : Objective: To investigate childhood, teenage and young adult cancer diagnostic pathways during the first wave of the COVID-19 pandemic in England. Design: Population-based cohort study. Setting and participants: QResearch, a nationally representative primary care database, linked to hospital admission, mortality and cancer registry data, was used to identify childhood, teenage and young adult cancers (0–24 years) diagnosed between 1 January 2017 and 15 August 2020. Main outcomes: Main outcomes of interest were: (1) number of incident cancer diagnoses per month, (2) diagnostic, treatment time intervals and (3) cancer-related intensive care admissions. Results: 2607 childhood, teenage and young adult cancers were diagnosed from 1 January 2017 to 15 August 2020; 380 were diagnosed during the pandemic period. Overall, 17% (95% CI −28.0% to −4.0%) reduction in the incidence rate ratio of cancers was observed during the pandemic. Specific decreases were seen for central nervous system tumour (−38% (95% CI −52% to −21%)) and lymphoma (−28% (95% CI −45% to −5%)) diagnoses. Additionally, childhood cancers diagnosed during the pandemic were significantly more likely to have intensive care admissions (adjusted OR 2.2 (95% CI 1.33 to 3.47)). Median time-to-diagnosis did not significantly differ across periods (+4.5 days (95% CI −20.5 to +29.5)), while median time-to-treatment was shorter during the pandemic (−0.7 days (95% CI −1.1 to −0.3)). Conclusions: Collectively, our findings of a significant reduction in cancer diagnoses and increase in intensive care admissions provide initial insight into the changes that occurred to childhood, teenage and young adult cancer diagnostic pathways during the first wave of the pandemic. Abstract : This study investigated children and young people diagnosed with cancer during the first wave of the COVID-19 pandemic in England. It reported a reduction in the incidence-rate-ratio of cancers and that the childhood cancers diagnosed during the pandemic were significantly more likely to have intensive care admissions.